Incidental Pancreatic Lipomas Diagnosed by Computed Tomography - Hasbahceci, Mustafa; Erol, Cengiz; Basak, Fatih; Barman, Ahmet; Seker, Mehmet (My University, 2014)
Objective: Fatty tumours of the pancreas are rarely reported. With the advent of the imaging techniques, diagnosis of such tumours based on radiologic imaging is increasing.